Developing knowledge management systems with an active expert methodology - Sandahl, Kristian (Linköping studies in science and technology. Dissertations ;, 1992)
Abstract: "Knowledge Management, understood as the ability to store, distribute and utilize human knowledge in an organization, is the subject of this dissertation. In particular we have studied the design of methods and supporting software for this process. Detailed and systematic description of the design and development processes of three case-study implementations of Knowledge Management software are provided. The outcome of the projects is explained in terms of an Active Expert development methodology, which is centered around support for a domain expert to take a substantial responsibility for the design and maintenance of a Knowledge Management system in a given area of application.